A qualitative exploration of the unmet psychosocial rehabilitation needs of cancer survivors in China. Issue 8 (3rd November 2015) - Wang, Ji‐Wei; Shen, Qian; Ding, Ning; Zhang, Tian‐Rui; Yang, Zhi‐Qi; Liu, Cong; Chen, Si‐Jia; Berry, Helen Louise; Yuan, Zheng‐Ping; Yu, Jin‐Ming
Abstract: Objective: This study explores the unmet psychosocial rehabilitation needs of cancer survivors. Methods: Sixty‐eight cancer survivors from the Shanghai Cancer Rehabilitation Club in China participated in one of the eight focus groups. These were transcribed verbatim, coded using thematic analysis and analysed using NVivo 10. Results: Five main themes were identified: the need for (1) better information: Chinese cancer survivors find it difficult to sort and evaluate the overwhelming mass of information with which they are confronted; (2) psychological support: survivors fear cancer relapse and neighbours' discrimination against them; support from other cancer survivors can relieve the stress; (3) support for survivors' families: like the survivors, family members are under great but usually unacknowledged pressure; (4) improved health and medical services: community health service centres provide little medical, informational or psychological support for cancer survivors, who seek and expect more communication with doctors; and (5) assistance with the financial burden: costs of treatment and lack of adequate medical insurance cause substantial financial pressure for survivors. Conclusions: This study shows that, in addition to their illness, Chinese cancer survivors experience a range of stresses related to their financial circumstances, lack of reliable and summarised information, poor access to support and services (including for their families) and discrimination. Support from families seems to improve survivors' ability to cope. Cancer survivors (and their families) need an integrated package of support from their families, doctors and other service providers, hospitals and communities. These findings can inform approaches to continuing care for cancer survivors. Copyright © 2015 John Wiley & Sons, Ltd.